The Stages of Tri Ning Danu Tourism Destination Development Based on Tourism Capital - Sunarta, I Nyoman; Sukma Arida, I Nyoman; Adikampana, I Made; Nugroho, Saptono (Udayana Journal of Social Sciences and Humanities; Vol 2 No 1 (2018): UJoSSH, Feburary 2018DO - 10.24843/UJoSSH.2018.v02.i01.p10, 2018)
This article aims to determine the life cycle of tourist destinations in three lakes: Beratan, Buyan, and Tamblingan or referred to as Tri ning Danu, based on tourism capital. This study was conducted considering the research about the lake-based tourism is still very limited, especially in Indonesia. The analysis was carried out using the model of the Tourist Area Life Cycle (TALC) introduced by Butler and the conception of tourism capital inspired by Bourdieu. The integration of both produces a profile of the position or stage of Tri ning Danu tourist destination development more adequately. This approach is relatively new as a breakthrough effort to get rid of conventional reports on the destination developments that generally rely solely on TALC. It is expected that with the added of tourism capital variable will get a more comprehensive view of destination development stage. The results of the stage of Tri ning Danu tourist destination development based on the tourism capital, as follows: Consolidation Stage for Beratan Lake, Involvement Stage for Buyan Lake, and Exploration Stage for Tamblingan Lake.